2016
DOI: 10.1149/07515.0379ecst
|View full text |Cite
|
Sign up to set email alerts
|

Intervalence Charge Transfer of the Nb(V)/Nb(IV) Redox Couple in Alkali Chloride Melts: Experiment and Quantum-Chemical Calculations

Abstract: The standard rate constants of charge transfer (k s) for the Nb(V)/Nb(IV) redox couple in KCl-NbCl5 and CsCl-NbCl5 chloride melts are determined. The Nb(V) electrochemical reduction process in the NaCl-KCl-NbCl5 melt was shown being reversible; hence, the determination of k s appeared impossible. Values of k s in the KCl-NbCl5 melt are higher than those in the CsCl-NbCl5 one. Previously, in a quantum-chemical calculations of nM+·[NbCl6] model systems (M = N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The diffusion coefficients decrease with a change of the composition of the second coordination sphere from sodium to cesium. Similar dependencies for D values are well known (9,10). It is associated with a decrease of the counter-polarizing effect during the transition from Na to Cs in second coordination sphere of the samarium complexes, which in turn causes a decrease of the metalligand bond length and increase the samarium complexes stability.…”
Section: Resultssupporting
confidence: 70%
“…The diffusion coefficients decrease with a change of the composition of the second coordination sphere from sodium to cesium. Similar dependencies for D values are well known (9,10). It is associated with a decrease of the counter-polarizing effect during the transition from Na to Cs in second coordination sphere of the samarium complexes, which in turn causes a decrease of the metalligand bond length and increase the samarium complexes stability.…”
Section: Resultssupporting
confidence: 70%
“…[62][63][64] Quantum-chemical calculations for explanation of this phenomenon are needed. 58,59,65 Conclusions Electrochemical behavior of the Sm(III)/Sm(II) redox couple was studied in NaCl-KCl-SmF 3 , KCl-SmF 3 and CsCl-SmF 3 melts by cyclic voltammetry. It was found that the redox process was reversible in NaCl-KCl-SmF 3 , KCl-SmF 3 and CsCl-SmF 3 up to the scan rate 1.0 V s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…A number of papers have investigated the effect of the electrode surface on electrochemical electron transfer by quantum-chemical methods (4,8,11,19). Quantumchemical studies of electron transfer in various melts are presented in (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%